Celpe-Bras preparation course at UNILA - Ferreira, Laura Marcia Luiza (Guará Journal, 2023)
Portuguese and Spanish are the working languages ​​of the University for Latin American Integration (UNILA), which has institutional bilingualism as one of its pillars. In this text, I describe the experience of coordinating the preparatory course for the Certificate of Proficiency in Portuguese for Foreigners (Celpe-Bras), held in the first and second semesters of 2019 within UNILA. I first present information on activities related to the Celpe-Bras exam at UNILA, such as exam administrations and the institution's first Celpe-Bras exam preparation courses. I then discuss the process of developing the methodology that guided the course editions during 2019 and its results, both for the students and for the training of future language teachers. The initiative benefited future test-takers from the university's internal community and the Triple Frontier region, and simultaneously provided a mandatory internship for future teachers, fostering literacy in language assessment. The report is expected to contribute to the documentation of Portuguese language promotion initiatives in university settings, as well as provide information for the development of new preparatory courses for proficiency exams.
Keywords: Teacher training; Assessment literacy; Celp-Bras